Ganglioglioma of Conus Medullaris—A Rare Case - Kumar, Sushil; Misra, Rajneesh; Kumar, Kundan; Sharma, Sandeep (Indian Journal of Neurosurgery, 2019)
AbstractGangliogliomas favor the temporal lobe. They are rarely reported in the spinal cord. Ganglioglioma of the conus medullaris is very rare. An 11-year-old boy presented with progressive weakness of bilateral lower limbs. Clinical examination and radiologic investigations revealed a lesion in the conus medullaris with an exophytic component involving the cauda equina roots. The lesion was excised near totally. Its histopathologic examination revealed it to be a ganglioglioma. Gangliogliomas of the conus medullaris are rare lesions. Subtotal or near-total excision with preservation of the function should be the aim of the surgical intervention. Because preoperative function largely dictates the postoperative course, it is advisable to intervene early at the first hint of neurologic compromise.
Keywords: ganglioglioma; intramedullary; exophytic; conus medullaris